Corporate Philanthropy and Firm Performance Relationship – Socio- Political and Government Control Effects - Lam, Sze-Sing; Hung, Pauline Hie-Yiin; Choi, Samuel Ping-Man (Asian Journal of Business and Accounting, 2022)
Manuscript type: Research Paper Research aims: This study aims to examine the impacts of socialpolitical context and government control on the relationship between corporate philanthropy and firm performance using the listed firms’ data on the Hong Kong Stock Exchange (HKEX). Design/Methodology/Approach: This study uses multiple regression analysis to study the relationship between corporate philanthropy and firm performance using 2012-2018 Hong Kong listed firm data. Empirical results show a positive association between the current and lagged corporate philanthropy and financial performance. Subgroup analysis shows that the relationship is contingent on the socio-political and government control factors. Our subgroup analysis reveals that Hong Kong firms benefit more from corporate philanthropy than Mainland China firms, and non-government control mainland private firms have a stronger positive relationship than the state-owned enterprises. Our results support social impact theory and political connection theory. Theoretical contribution/Originality: Our study bridges the gap of prior studies on the philanthropy-corporate finance relationship by isolating the separate effect of socio-political context impact and government ownership. We believe we are the first study in this respect. Our findings validate the results of prior studies in general and suggest the empirical results based on transitional economy data is, to some extent, generalisable. Practitioner/Policy implication: Contemporary data provides empirical evidences that corporate philanthropy could elicit positive responses from stakeholders to bolster corporate financial performance, except firms under government control. The positive impact of donation was immediate with a lasting effect as suggested in the literature and the result would be relevant for regulators in formulating policies regarding corporate social performance. Research limitation/Implication: Similar to previous studies, corporate philanthropy is proxy by the monetary amount of donation in this study. However, the context of corporate philanthropy very often goes beyond monetary donations and the findings may not apply to firms making substantial non-monetary donations. Keywords: Corporate Philanthropy, Corporate Social Responsibility, Firm Performance, Socio-political Context, State-owned Enterprises. JEL Classification: M14